Identification of MAIN, a factor involved in genome stability in the meristems of Arabidopsis thaliana. (29th May 2013) - Wenig, Ulrich; Meyer, Stefan; Stadler, Ruth; Fischer, Simon; Werner, Dagmar; Lauter, Anja; Melzer, Michael; Hoth, Stefan; Weingartner, Magdalena; Sauer, Norbert
Summary: Stem cells in the root and shoot apical meristem provide the descendant cells required for growth and development throughout the lifecycle of a plant. We found that mutations in the Arabidopsis MAINTENANCE OF MERISTEMS ( MAIN ) gene led to plants with distorted stem cell niches in which stem cells are not maintained and undergo premature differentiation or cell death. The malfunction of main meristems leads to short roots, mis‐shaped leaves, reduced fertility and partial fasciation of stems. MAIN encodes a nuclear‐localized protein and is a member of a so far uncharacterized plant‐specific gene family. As main mutant plants are hypersensitive to DNA‐damaging agents, expression of genes involved in DNA repair is induced and dead cells with damaged DNA accumulate in the mutant meristems, we propose that MAIN is required for meristem maintenance by sustaining genome integrity in stem cells and their descendants cells.